2024
DOI: 10.1038/s41598-024-55530-7
|View full text |Cite
|
Sign up to set email alerts
|

Academic resilience, self-efficacy, and motivation: the role of parenting style

Ye Shengyao,
Hashem Salarzadeh Jenatabadi,
Ye Mengshi
et al.

Abstract: Previous research has found that parenting style influences academic resilience. Nonetheless, few studies have focused on the mechanism underlying the relationship between parenting style and academic resilience. This study aims to examine the relationship between adolescents' parenting style and academic resilience, drawing upon the framework of Social Cognitive Theory. Specifically, it wants to explore the mediating roles of self-efficacy and academic motivation in this relationship. The participants were 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…(31) Según esta teoría, la autoeficacia, o la creencia en la propia capacidad para realizar una tarea, desempeña un papel crucial en la motivación y el comportamiento humano. (32) Cuando una persona tiene una autoeficacia alta en una tarea específica, como el rendimiento académico, tiende a sentirse más confiada en su capacidad para lograr buenos resultados. (33,34) Esta confianza aumentada no solo impulsa la motivación intrínseca, sino que también reduce la tendencia a procrastinar, ya que la persona se siente más segura y capacitada para enfrentar sus responsabilidades académicas de manera efectiva.…”
Section: Discussionunclassified
“…(31) Según esta teoría, la autoeficacia, o la creencia en la propia capacidad para realizar una tarea, desempeña un papel crucial en la motivación y el comportamiento humano. (32) Cuando una persona tiene una autoeficacia alta en una tarea específica, como el rendimiento académico, tiende a sentirse más confiada en su capacidad para lograr buenos resultados. (33,34) Esta confianza aumentada no solo impulsa la motivación intrínseca, sino que también reduce la tendencia a procrastinar, ya que la persona se siente más segura y capacitada para enfrentar sus responsabilidades académicas de manera efectiva.…”
Section: Discussionunclassified
“…2023 Self-Efficacy. Self-Efficacy is a psychological concept that describes a person's confidence in their capacity to accomplish tasks (Shengyao et al, 2024). Academic Motivation.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Research has indicated a favorable correlation between academic motivation and self-efficacy. (Shengyao et al, 2024). When students believe in their capacities to succeed, they are more likely drive them to pursue academic goals and all way to face the challenges.…”
mentioning
confidence: 99%